Strategi Pengembangan Universitas Wijayakusuma Purwokerto - Suyudi Suyudi (Media Aplikom, 2010)
Dynamic growth that happened claim the organization to can to expand and adapt to the actual growth that happened. That way also in higher education management, what ever always to expand to. In relation of those things, this research was aim to for describe and analyse the development of Wijayakusuma University Purwokerto in the effort to become certifiable private college. Research method used qualitative. Data collecting method used indepth interview, observation, and documentation. Informan chosen done by purposive. Data analyse used interactive model of analysis and data validity used triangulation with model source. Wijayakusuma University have developed a number of steps and policis in order to organizational development so that can become the certifiable private college. In HELTS framework, the effort of organizational development in Wijayakusuma University done by make-up of competitiveness, decentralize and autonomous and also organizational health. Various effort which have the in the reality not yet earned to give the significant contribution to university progress. Degradation sum up the student still be happened. It was indicated the low enthusiasm of society to become Wijayakusuma University student. Endless internal conflict and negativity perception expanding in society to Wijayakusuma University and also low competitiveness likely still become the dominant factor making Wijayakusuma University not yet earned to awaken from down.